3D DOCUMENTATION OF A HISTORICAL MONUMENT USING TERRESTRIAL LASER SCANNING CASE STUDY: BYZANTINE WATER CISTERN, ISTANBUL - Temizer, T.; Nemli, G.; Ekizce, E.; Ekizce, A.; Demir, S.; Bayram, B.; Askin, F. H.; Cobanoglu, A. V.; Yilmaz, H. F. (COPERNICUS GESELLSCHAFT MBH, 2013)
3D modelling of architectural structures for monitoring, conservation and restoration alterations in heritage sites has special challenges for data acquisition and processing. The accuracy of created 3D model is very important. In general, because of the complexity of the structures, 3D modelling can be time consuming and may include some difficulties. 3D terrestrial laser scanning technique is a reliable and advantageous method for reconstruction and conservation of monuments. This technique is commonly acknowledged due to its accuracy, speed and flexibility. Terrestrial laser scanners can be used for documentation of the cultural heritage for the future. But it is also important to understand the capabilities and right conditions of use and limitations of this technology. Istanbul is a rich city with cultural monuments, buildings and cultural heritage. The presented study consists of documentation of a Byzantine water cistern situated underground the court of Sarnicli Han building. The cistern which represents a very good living example of its period has been modelled in 3D by using terrestrial laser scanning technology and the accuracy assessment of this modelling is examined.
Keywords: Cultural Heritage; Terrestrial Laser Scanning; 3D Modelling; Point Cloud; MESH; Physical Geography; Remote Sensing; Imaging Science & Photographic Technology